RANCANG BANGUN ALAT PENDETEKSI KONDISI TELUR AYAM BERBASIS MIKROKONTROLER ATMEGA 32 DENGAN SENSOR CAHAYA - Afdal Tahir; Mery Subito; Agustinus Kali (Foristek, 2019)
When consumers buy eggs, consumers should be more careful choosing the egg because there are some eggs that the quality has been decreased or the eggs are damaged and cannot be consumed anymore. This is caused by the length of egg storage time and didn’t have a tool that capable to detect the condition of the egg. People or egg breeders / entrepreneurs habit on looking the quality of eggs still use manual way, as a result it takes a long time because it must select the eggs condition one by one. The purpose of this research is to design and make the detection tool of chicken egg condition with ATmega 32 microcontroller using light sensor, so that the time efficiency and the result of egg selection becomes faster. . The use of tools is very easy and simple so that consumers or breeders / entrepreneurs can use it. Then to simplify and speed up the selection time of chicken eggs breeder or entrepreneur to distinguish good and damaged egg condition.